The impact of regular physical activity on vertebral fractures: Korean nationwide population-based cohort study - Sangsoo Han; Sungwoo Choi; Hae-Dong Jang; Jiwon Park; Kyungdo Han; Sangun Nah; Dong Hun Suh; Dong Sub Im; Jae-Young Hong (BMC Musculoskeletal Disorders)
Abstract Background Vertebral fractures are a common medical issue. Physical activity helps improve bone health and manage the risk of fractures. However, much controversy exists about the association between physical activity and vertebral fractures. Therefore, we aimed to investigate the association between changes in regular physical activity (RPA) and vertebral fractures. Methods This study was a nationwide, observational cohort study based on claim data from the Korean National Health Insurance Service. Physical activity level was obtained from self-reported questionnaires from 2009 to 2012. Participants were divided depending on their levels of physical activity and the occurrence of vertebral fractures from 2013 to 2016 was recorded. Results The group with sufficient RPA, compared to the Insufficient group (incidence rate showed a decrease of 1.93/1,000 PY; adjusted HR (aHR): 0.83; 95% CI: 0.81–0.84), had a reduced risk of vertebral fracture. From the perspective of RPA changes, the Continuous Sufficient group had an aHR of 0.74, 95% CI 0.72–0.76, and the Increased group had an aHR of 0.87, 95% CI 0.85–0.88. The Decreased group had an aHR of 0.94, 95% CI 0.92–0.95. Conclusion The degree of RPA could reduce the risk of vertebral fracture. Continuous sufficient RPA helped lower the risk of vertebral fracture.